2011
DOI: 10.1509/jmkr.48.spl.s23
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Saving Behavior Through Age-Progressed Renderings of the Future Self

Abstract: Many people fail to save what they need to for retirement (Munnell, Webb, and Golub-Sass 2009). Research on excessive discounting of the future suggests that removing the lure of immediate rewards by pre-committing to decisions, or elaborating the value of future rewards can both make decisions more future-oriented. In this article, we explore a third and complementary route, one that deals not with present and future rewards, but with present and future selves. In line with thinkers who have suggested that pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
432
3
14

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 520 publications
(456 citation statements)
references
References 82 publications
7
432
3
14
Order By: Relevance
“…Virtual reality studies have demonstrated that self-avatars with different ages [Hershfield et al 2011], shapes [Piryankova et al 2014], and races [Kilteni et al 2013] alter participants' perception and attitudes. Future work could investigate if self-perception of strength and power can also be influenced by a modified self-avatar.…”
Section: Discussion and Summarymentioning
confidence: 99%
“…Virtual reality studies have demonstrated that self-avatars with different ages [Hershfield et al 2011], shapes [Piryankova et al 2014], and races [Kilteni et al 2013] alter participants' perception and attitudes. Future work could investigate if self-perception of strength and power can also be influenced by a modified self-avatar.…”
Section: Discussion and Summarymentioning
confidence: 99%
“…Behavioral economic theories have studied impulsiveness from the perspective of present bias and a discounting of the future, which has informed a dual self theory of impulsiveness (Fudenberg and Levine 2006). Establishing a connection and interaction between present and future self by means of age-progressed photographs can increase people's likelihood to accept delayed monetary rewards over immediate rewards (Hershfield, Goldstein, Sharpe, Fox, Yeykelis,Carstensen, and Bailenson 2011).…”
Section: Current Directions: Predicting Impulsive Consumer Behaviormentioning
confidence: 99%
“…Temporal discounting, or the tendency to undervalue future risks and rewards as compared with more proximal events or states, may contribute to these errors (53). Fortunately, emerging evidence suggests that this prevalent bias may be surmountable (54)(55)(56). This study demonstrates that patients or potential surrogate decision makers facing a preference-sensitive medical decision attempt to engage in future-oriented thinking, but that they often err in systematic ways.…”
Section: Discussionmentioning
confidence: 85%